Assessment of powdery mildew resistance in wild barley (Hordeum spontaneum L.) populations in the aegean region of Turkey - Zeybek, A.; Yiğit, F. (Phytoprotection, 2002)
In a study of resistance to powdery mildew, we investigated three populations of Hordeum spontaneum using leaf segment test. For comparison of the reactions, we used 44 barley lines as differentials representing most of the resistance used in barley breeding. The H. spontaneum accessions were infected with 21 isolates selected for their reactions on the differential barleys. The results of H. spontaneum collections did not show any similarities with differential barleys used. Resistance reactions were very rare. There was no resistance to 13 out of the 21 isolates. Horizontal resistance was noticed in most of H. spontaneum lines.